HADIS DAN KESARJANAAN TIMUR - Alwy Fadly Harahap (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
Goldziher''s view of hadith is that most hadiths cannot be trusted as a whole as a source of teachings sourced from the Prophet. Most of the hadith material in the hadith book collection is sourced from the results of the religious, historical and social development of Islam which is sourced from hadith figures in the first two centuries. Library research called the scholar skeptic as a scholar who analyzed the problem of authenticity of hadith as a scholar who used an "Orientalist" approach, then reinforced by the next generation called "Revisionist" represented by Patricia Crone and Michael Cook. The last so-called school chooses a slightly different topic, for example about the Charter of Medina, wala'', and others. Then came a new "school" that corrected the two schools above, which Brown called the school of "Revaluation". The fundamental doubts about the history of early Muslims raised by skeptics and revisionists have aroused an unprecedented defense of the narrative of hadith and the origins of Islam for certain Western scholars, presumably the revaluasists.The early generation of Western scholars, with slightly different arguments and backgrounds, tended to state that in general, if not all, of the hadith circulating among Muslims became canonic hadith books and some in the book of Tafsir and the book of Sirah, were fabricated by those who narrated the hadith. They are called skeptics. Nevertheless, the statement is not entirely agreed upon by Western scholars. When the skeptics'' reasoning changed hands and continued in the middle of the 20th century, then thoughts such as Nabila Abbot and Fueck also appeared, countering these skeptical thoughts.